Survei Kebugaran Jasmani Siswa Smp Negeri 2 Kerinci Pada Kegiatan Ekstrakurikuler Futsal - Aldino Wira Praja; Muhammad Ali; Anggel Hardi Yanto (Jurnal Riset Multidisiplin Edukasi, 2025)
The results of the researcher's observations on the Extracurricular Futsal players at SMP Negeri 2 Kerinci during the match, there were still many players who were slow to move when taking the ball from the opponent, especially in the second half, even though the training they had done was maximized, but from the coach's statement, the players' backgrounds were different and their daily activities were also different, so that their physical condition was also different. Seeing these conditions, the researcher wanted to conduct a study that aimed to analyze the physical condition of the players, so that the lack of physical condition could be used as a review by the coach to focus more on the fitness condition of the players. This study is a descriptive study, namely a study that aims to find out and get a picture or the real reality of the condition of the object being studied without any intention to draw conclusions that apply in general. The sample used in this study used a total sampling population study because the population was relatively small so that all the population was used as a sample totaling 23 people. Based on the analysis of fitness test results data 50 meters from 13 people who have a category Very Good as many as 1 person with a percentage of 8%, Good as many as 10 people with a percentage of 77%, who have a moderate category as many as 2 people with a percentage of 15%, physical fitness standing broad jump which has a good category as many as 3 people with a percentage of 23%, moderate category as many as 9 people with a percentage of 69%, less category as many as 1 person with a percentage of 8%, physical fitness test lying sitting which has a good category as many as 8 people with a percentage of 62%, who have a moderate category as many as 5 people with a percentage of 38%, physical fitness Shuttle Run test which has a good category as many as 3 people with a percentage of 23%, who have a moderate category as many as 9 people with a percentage of 69%, who have a less category as many as 1 person with a percentage of 8%. The conclusion of this study is that the physical fitness of students of SMP Negeri 2 Kerinci in Futsal Extracurricular Activities is in the good category.